Selection of keratometric data for the IOL toricity calculation - S.V. Shukhaev (Офтальмохирургия)
Purpose. To elaborate the customized principle of determining the actual zone of the corneal astigmatism based on keratotopographic data and compare the accuracy of calculating the toric IOL according to the actual zone and conventional keratometry. Material and methods. The study included 48 patients (48 eyes) who underwent toric IOL implantation. 3–6 months (5.1±0.6) after surgery, all patients were measured the residual refractive astigmatism. The toric IOL was retrospectively calculated according to the data of the actual keratotopographic zone determined by the proposed method (1st group) and according to conventional keratometry (2nd group). Vector and centroid analyses were used to estimate the error in calculating the IOL toricity. Results. The principles of determining the actual zone are based on the assumption that maximum visual acuity and visual quality can be achieved when the regularity of astigmatism in the central parts of the cornea corresponds to the regularity of toric IOL. The mean diameter of the selected actual zone was 2.93±0.61 (from 2.0 to 4.3 mm respectively). The average vector error of toricity calculation in 1st group was 0.30±0.31, in 2nd group – 0.42±0.30 (p=0.006). Centroid analysis showed similar values of centroid error in 1st group and 2nd group (0.09 and 0.08), while the dispersion was higher in 2nd group (0.42 and 0.51, respectively). Conclusion. The customized principle of selecting the actual zone according to topographicmaps of the cornea showed a more accurate calculation of the IOL toricity compared with the use of conventional keratometry data.